Resistance and control in Pakistan - Ahmed, Akbar S. (London, 1991)
How can people in the West make sense of contemporary unrest in the Muslim world? Is Islamic fundamentalism to be understood purely in religious terms? In Resistance and Control in Pakistan, one of the world's leading authorities on Islam, Akbar S. Ahmed, illuminates what is happening in the Muslim world today and assesses the underlying causes. He does this by telling the dramatic story of the revolt of the Mullah of Waziristan in northwest Pakistan and by placing it within the context of other movements occurring elsewhere in the Islamic world. He also examines the social structure and operative principles in Muslim society and scrutinizes the influence of religion in a society that is undergoing modernization. Till now, there has been little available literature on this topic. This book, written by an eminent scholar with an international reputation fills this gap, giving students of politics, sociology and Asian studies a revealing examination of the Muslim world today.
Keywords: Resistance